Geometric properties and gravitational potential of Reissner-Nordstrom-De Sitter space-time - Villata, Franco (2023)
This work seeks to give a description of the geometry of space-time and its fundamental properties outside the Reissner-Nordstrom-De Sitter (RNdS) black hole in relation to their respective event horizons. For this purpose, we conduct the corresponding transformation to the Kruskal coordinates, which allows us to fully and consistently analyze from the physical point of view the behavior of the causal structure around the mentioned horizons and throughout the referred space-time continuum. Subsequently, using Einstein's field equations and jointly those that govern the behavior of gravitational fields in the non-relativistic Newtonian limit, it is possible to obtain the exact form of the gravitational potential of RNdS. Finally, with this last expression, we can analyze both qualitatively and quantitatively the true influence that a positive cosmological constant can have within the gravitational field produced by a charged mass distribution, spherically symmetrical and at rest.